2016
DOI: 10.1186/s12863-016-0332-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in peripheral tissue of schizophrenia and bipolar disorder: a systematic review

Abstract: BackgroundIncreasing evidence suggests the involvement of epigenetic processes in the development of schizophrenia and bipolar disorder, and recent reviews have focused on findings in post-mortem brain tissue. A systematic review was conducted to synthesise and evaluate the quality of available evidence for epigenetic modifications (specifically DNA methylation) in peripheral blood and saliva samples of schizophrenia and bipolar disorder patients in comparison to healthy controls.MethodsOriginal research artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 79 publications
1
51
0
4
Order By: Relevance
“…This might be due to the lack of control for genotype, differences in the tissue being analyzed, sample heterogeneity, as well as still insufficient sample sizes. The variability between studies has also been pointed out by a recent systematic review (Teroganova et al, 2016) of findings in peripheral tissues (blood and saliva), especially in regards to the different methods used for the assessment of DNA methylation, DNA extraction, and lack of control for potential effects of clinical variables (such as diet, exercise, smoking, and ethnicity).…”
Section: Perspectivesmentioning
confidence: 99%
“…This might be due to the lack of control for genotype, differences in the tissue being analyzed, sample heterogeneity, as well as still insufficient sample sizes. The variability between studies has also been pointed out by a recent systematic review (Teroganova et al, 2016) of findings in peripheral tissues (blood and saliva), especially in regards to the different methods used for the assessment of DNA methylation, DNA extraction, and lack of control for potential effects of clinical variables (such as diet, exercise, smoking, and ethnicity).…”
Section: Perspectivesmentioning
confidence: 99%
“…DNA methylation mainly occurs at the 5′ position of the cytosine base followed by a guanine base that is called CpG [9]. A number of studies have demonstrated aberrant DNA methylation in SCZ [10,11,12,13,14,15,16,17,18]. Furthermore, growing evidence suggests that DNA methylation may be involved in the therapeutic efficacy of atypical antipsychotic drugs [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to study epigenetic signatures in humans involve both studies of post-mortem brains but also peripheral tissues (blood and saliva) (Teroganova et al, 2016). In comparison to other major psychiatric disorders (i.e., schizophrenia and major depressive disorder) epigenetic contributions to various BD phenotypes remains largely understudied.…”
Section: Introductionmentioning
confidence: 99%